2020
DOI: 10.3390/ijms21145147
|View full text |Cite
|
Sign up to set email alerts
|

ATG4 Mediated Psm ES4326/AvrRpt2-Induced Autophagy Dependent on Salicylic Acid in Arabidopsis Thaliana

Abstract: Psm ES4326/AvrRpt2 (AvrRpt2) was widely used as the reaction system of hypersensitive response (HR) in Arabidopsis. The study showed that in npr1 (GFP-ATG8a), AvrRpt2 was more effective at inducing the production of autophagosome and autophagy flux than that in GFP-ATG8a. The mRNA expression of ATG1, ATG6 and ATG8a were more in npr1 during the early HR. Based on transcriptome data analysis, enhanced disease susceptibility 1 (EDS1) was up-regulated in wild-type (WT) but was not induced in atg4a4b (ATG4 deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Yoshimoto et al found that BTH could induce senescence and cell death in atg5 mutants but could not induce senescence and cell death in atg5 npr1 double mutants, indicating that the cell death phenotype in atg5 mutants depended on NPR1 under SA induction [57]. Our previous study also found that ATG4 promoted NPR1 degradation by inhibiting the consumption of free SA [61]. In recent years, the relationship between ATGs and NPR1 has been gradually revealed (Table 2), but there are still many problems to be solved.…”
Section: Relationship Between Atgs and Npr1mentioning
confidence: 66%
See 2 more Smart Citations
“…Yoshimoto et al found that BTH could induce senescence and cell death in atg5 mutants but could not induce senescence and cell death in atg5 npr1 double mutants, indicating that the cell death phenotype in atg5 mutants depended on NPR1 under SA induction [57]. Our previous study also found that ATG4 promoted NPR1 degradation by inhibiting the consumption of free SA [61]. In recent years, the relationship between ATGs and NPR1 has been gradually revealed (Table 2), but there are still many problems to be solved.…”
Section: Relationship Between Atgs and Npr1mentioning
confidence: 66%
“…Studies have found that NPR1 regulates ATGs expression. NPR1 inhibited the mRNA expression of ATG1, ATG6, and ATG8a during the early HR induced by Psm ES4326/AvrRpt2 [61]. SA analog benzothiadiazole (BTH) was confirmed to induce autophagy through the NPR1-dependent signaling pathway, and NPR1, NPR3, and NPR4 are jointly involved in the regulation of autophagosomes [91].…”
Section: Relationship Between Atgs and Npr1mentioning
confidence: 99%
See 1 more Smart Citation
“…ATG4 inhibits SA consumption resulting in the inhibition of NPR3 (non-expressor of pathogenesis-related genes 3) synthesis and enhanced expression of NPR1, which inhibits autophagy durin g AvrRpt2 affection. These results indicate that ATG4 mediates AvrRpt2 -induced autophagy dependent on SA ( Gong et al, 2020 ). Therefore, the role of autophagy in the immune response depends on what pathogen signals the plant cell receives.…”
Section: Regulation Of Autophagy By Biotic Stress Signalsmentioning
confidence: 89%
“…In Nicotiana benthamiana autophagy-deficient plants, HR-PCD spreads uncontrollably to uninfected cells ( Liu et al, 2005 ). In Arabidopsis , Psm ES4326/ AvrRpt2 can trigger autophagy-dependent HR via the EDS1 (enhanced disease susceptibility 1) pathway, but NPR1 (non-expressor of pathogenesis-related genes 1) suppresses the autophagy flux ( Gong et al, 2020 ). In Arabidopsis atg4a4b double mutant, total SA (salicylic acid) content decreased and free SA unchanged compared with wild type after AvrRpt2 infection, indicating that ATG4 can suppress the consumption of free SA.…”
Section: Regulation Of Autophagy By Biotic Stress Signalsmentioning
confidence: 99%